Strengthening CRM based on live chat for customer service performance audits - Wisswani, Ni Wayan; Ciptayani, Putu Indah; Saptarini, Ni Gusti Ayu Putu Harry (Matrix : Jurnal Manajemen Teknologi dan Informatika, 2025)
The management of relationships between customers and companies is still largely carried out conventionally. Communication between companies and customers tends to be slow and is highly limited by time constraints. This condition makes it more difficult to maintain good relationships between customers and companies, even though such relationships are crucial for business continuity. Conventional communication methods also hinder the monitoring of customer service performance toward customers. Technology-based Customer Relationship Management (CRM) can be a strategic solution to overcome the weaknesses in managing and maintaining these relationships. The purpose of this research is to implement a CRM application using real-time live chat technology to enable faster customer service responses and facilitate service monitoring for the company’s management, thereby making performance auditing of customer service easier. The CRM live chat application in this study was developed using the waterfall method and implemented using Visual Studio Code, Laragon as a web server, PHP, JavaScript, MySQL, and Pusher. The implementation was tested using Blackbox testing and User Acceptance Testing (UAT), with the results showing that all functions related to real-time communication and service monitoring operated properly, and the user satisfaction rate reached 85.8%.